Multimodal optical imaging of iris flocculi in three consecutive generations: a case report - Jiang, Anna; Liang, Licong; She, Kaiqin; Lu, Fang (Frontiers in Medicine, 2024)
Background: Multiple pigmented epithelial cysts at the edge of pupils, i.e. iris flocculi, in both eyes, are rare ocular diseases. It has been demonstrated that this disease can be attributed to mutations in the smooth muscle αactin 2 (ACTA2) gene, which mainly affects the function of smooth muscle cells (SMCs). SMCs are components of the iris, aorta, and several other systemic organs. In addition, iris flocculi are strongly correlated with familial thoracic aortic aneurysm and dissection (TAAD), which is caused by the mutation of amino acid 149 in the ACTA2 gene. Case description: A 6-month-old Chinese boy was found to have iris flocculi during ocular fundus screening for premature infants. His mother, a 30-year-old Chinese woman with a history of aortic dissection, underwent an ophthalmic examination and was found to have iris flocculi. Whole exome sequencing revealed a heterozygous c.445C>T (p. Arg149Cys) mutation in ACTA2 in both the boy and his mother. After his family history was traced, the boy's grandfather was diagnosed with similar iris flocculi. Due to the absence of any ocular complications caused by iris flocculi in the cases, no special treatment was given, and regular follow-up was recommended. Conclusions: We reported one case of familial iris flocculi caused by a heterozygous missense mutation in ACTA2 (p. Arg149Cys), and presented multimodal optical images of both the iris and fundus in three consecutive generations. This case report enriched the clinical features of retinal vasculature and macula associated with the mutation in the amino acid 149 of the ACTA2 gene.In this work, we report 3 generations of familial iris flocculi caused by a heterozygous missense mutation in ACTA2 (p. Arg149Cys). Additionally, we present multimodal optical images of both the iris and fundus in three consecutive generations. This case report enriched the clinical features of retinal vasculature and macula associated with the mutation in the amino acid 149 of the ACTA2 gene.